Experimental Study of a Nonlinear Viscoelastic Model for Elastomeric Bushing in Torsional Mode - Lee, S.; Yeom, S.; Hong, S.; Woo, C. (Asian Journal of Chemistry, 2013)
Elastomeric bushing is a device to cushion the load and moment transmitted from the wheel to the frame of a vehicle in an automotive suspension system. The shape of the elastomeric bushing can be regarded as a hollow cylinder that is bonded to a solid shaft at its inner surface and a hollow sleeve at its outer surface. Because elastomeric bushing shows nonlinear viscoelastic phenomena, the nonlinear viscoelastic model should be used for simulations. In this study, a nonlinear viscoelastic model for the torsional mode of elastomeric bushing was examined and the relationship between the moment and rotational angle in an elastomeric bushing was derived from the experimental data. The nonlinear viscoelastic model for elastomeric bushing in torsional mode was confirmed to be useful by experimental comparisons under the working range.